2019
DOI: 10.1002/jcb.29435
|View full text |Cite
|
Sign up to set email alerts
|

NR2F1‐AS1 regulated miR‐423‐5p/SOX12 to promote proliferation and invasion of papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is an aggressive histological subtype of thyroid carcinoma (THCA), whose occurrence rate is high. The participation of long noncoding RNAs in the pathologies of cancers has attracted significant attention during the past decades. The purpose of the current study is to investigate the role of NR2F1 antisense RNA 1 (NR2F1‐AS1) in PTC. The expression of NR2F1 in THCA samples was analyzed by bioinformatics tool gene expression profiling interactive analysis. Levels of NR2F1‐AS1, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…In hepatocellular carcinoma, DLGAP1-AS1 has been confirmed to facilitate cell proliferation via the miR-486-5p/H3F3B axis (35). NR2F1-AS1 has been reported to play a role in papillary thyroid carcinoma (14), ESCC (12), endometrial cancer (15), hepatocellular carcinoma (36) and OS (16). In OS, NR2F1-AS1 has been identified to sponge miR-483-3p to upregulate FOXA1 and enhance the malignant properties of OS cells (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocellular carcinoma, DLGAP1-AS1 has been confirmed to facilitate cell proliferation via the miR-486-5p/H3F3B axis (35). NR2F1-AS1 has been reported to play a role in papillary thyroid carcinoma (14), ESCC (12), endometrial cancer (15), hepatocellular carcinoma (36) and OS (16). In OS, NR2F1-AS1 has been identified to sponge miR-483-3p to upregulate FOXA1 and enhance the malignant properties of OS cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…NR2F1-AS1 has also been reported to regulate the microRNA (miR)-338-3p/cyclin D1 axis to promote thyroid cancer progression (13). In papillary thyroid carcinoma, NR2F1-AS1 has been confirmed to exacerbate cell proliferation by regulating the miR-423-5p/SRY-box transcription factor (SOX)12 signaling pathway (14). In addition, in endometrial cancer, NR2F1-AS1 has been reported to sponge miR-363 and target SOX4 to play a role in cell proliferation and migration (15).…”
Section: Introductionmentioning
confidence: 99%
“…19 It has been found that miR-423-5p abnormally reduces in more aggressive TC phenotypes, which indicates that this miR may have a potential effect on inhibiting tumors. 20 As a member of the p21-activated kinase (PAK) family, PAK3 is a carcinogenic factor that regulates crucial cell behaviors and participates in the occurrence and progression of tumors such as TC. 21 In this paper, we observed highly expressed PVT1 in the tissues, serum and cells of patients with TC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in tongue squamous cell carcinoma, lncRNA CASC9 was demonstrated to affect cell proliferation, migration, and invasion via regulating miR-423-5p/SOX12 axes; 30 while in papillary thyroid carcinoma, it was found that lncRNA NR2F1-AS1 could regulate miR-423-5p/SOX12 to promote cell proliferation and invasion. 31 In the current study, we discovered that SOX12 was up-regulated in LUAD tissues and cell lines and contributed to LUAD cell proliferation as downstream target of TMPO-AS1/miR-326 pathway. Finally, we elucidated that transcription factor E2F1 contributed to the up-regulation of TMPO-AS1 in LUAD at transcriptional level.…”
Section: Discussionmentioning
confidence: 66%